The effects of road transportation on some physiological stress measures in goats - Rajion, Mohamed Ali; I., Mohamed Saat; Idrus, Zulkifli; Goh, Yong Meng (Asian-Australasian Association of Animal Production Societies, 2001)
A study to assess the physiological stress responses in goats that were subjected to road transportation was carried out using 10 Kacang crossbred does. Five does were transported in the morning with another five transported in the afternoon covering a distance of 46 km in an open-truck at an average speed of 55 km/h. Immediately following the road transportation, there were dramatic increases in neutrophi:lymphocyte ratios and plasma glucose concentrations but plasma cholesterol concentrations and body temperature were not affected. The neutrophil:lymphocyte ratios and plasma glucose concentrations appear to be reliable indicators of stress in goats.